Meditation and Communion with God Contemplating Scripture in an Age of Distraction - Davis, John Jefferson (Downers Grove, Ill IVP Academic, 2012)
John Jefferson Davis helps us recover the practice of meditation on Scritpure as he explores the biblical and theological foundations rooted in the arrival of "the age to come" in Jesus Christ. Davis gives us fresh and practical guidance on removing the
Keywords: Meditation -- Christianity